Comparison between laparoscopy and laparotomy in the management of ectopic pregnancy: a retrospective study - Singh, Suneeta; Sandhu, Namrita; Singh, Sanjay; Kumar, Praveen; Aziz, Atiya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Ectopic pregnancy is one of the most important causes of maternal mortality and morbidity in the first trimester of pregnancy. Objective of this study was to compare the safety, feasibility and advantage of laparoscopic approach with that of laparotomy in management of ectopic pregnancy. Methods: A retrospective study was conducted at two tertiary hospitals over a period of two years i.e.; from Aug 2015 to July 2017. Seventy-five patients who had histopathology confirmed tubal ectopic pregnancy were divided into two groups; laparoscopy (Group I, no-39) and laparotomy (Group II no-36). The main outcome measures were operative time, blood loss, and requirement of blood transfusion, requirement of analgesia and duration of hospital stay. Results: Seventy-five patients of ectopic pregnancy who were managed surgically were studied. There were 39 cases in laparoscopy group and 36 cases in laparotomy group. The incidence of ectopic pregnancy was 1.56% (out of all deliveries over 2 years). Ampullary region was the commonest site of ectopic pregnancy (74.6%). No difference was found in the two groups regarding age, site of tubal pregnancy, pre op Hb status and haemoperitoneum. Mean operating time was significantly shorter in the laparoscopy group 39 min (range 30 - 52 min) versus 50 min (range 40-60 min) in the laparotomy group. There was no difference between the groups regarding the treatment with blood products and perioperative complications. Hospital stay was significantly longer in the laparotomy group (3.5 days) as compared to 2 days in laparoscopy group. The duration of post op analgesia requirement was also longer in laparotomy group (4 days) as compared to 2 days in laparoscopy group. Conclusions: Laparoscopic management of ectopic pregnancy is a safe, effective and beneficial option in the hands of an experienced laparoscopic surgeon even in cases of massive haemoperitoneum. It definitely offers the advantage of shorter duration of surgery, faster post op recovery, shorter duration of hospital stays and lesser requirement of post op analgesia.